Pengembangan Pembelajaran Lempar Lembing Menggunakan Media Roket Pada Siswa Kelas VIII Sekolah Menengah Pertama Muhammadiyah 14 Kecamatan Makassar Kota Makassar - Wahyudin Wahyudin (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is to produce rocket learning media in class VIII of SMP Muhammadiyah 14 Makassar in improving Physical Education learning. This type of research is development research that is (1) analyzing products that will be developed from the results of field observations and literature reviews, (2) developing initial product forms, (3) expert evaluations using one physical education expert and one junior physical education instructor, and small-scale trials (10 students), using a questionnaire questionnaire then analyzed, (4) initial product revisions, (5) large-scale trials (32 students), (6) final product revisions after conducting large-scale field trials, (7 ) the final results of the rocket media for junior high school students grade VIII produced through the revision of large-scale field trials. The instrument used was a questionnaire questionnaire. The data analysis technique is descriptive percentages. The conclusion of this study is the results of the assessment of the experts namely, Physical Education experts 88% (good) and learning experts 83% (good), from a wide-scale trial results obtained questionnaires the average percentage of answer choices of 90 (very good). This rocket development media is effective for students of class VIII of SMP Muhammadiyah 14 Makassar. Suggestions: 1) this rocket media can be an alternative delivery of material, 2) rocket media can be used to achieve the goal of penasorkes, 3) the use of this media must pay attention to the safety and safety factors of students especially for students who play.